A ginger derivative, zingerone—a phenolic compound—induces ROS‐mediated apoptosis in colon cancer cells (HCT‐116). Issue 12 (12th November 2019) - Su, Ping; Veeraraghavan, Vishnu Priya; Krishna Mohan, Surapaneni; Lu, Wang
Abstract: Zingerone (ZO), an active phenolic agent derived from Zingiber officinale (Ginger), has many pharmacological properties such as antioxidant, antiangiogenic, and antitumor. However, its potential value in cancer and the mechanism by which ZO wields its therapeutic effects remain obscure. Therefore, in this current study, we explored the effects of ZO on suppressing cell proliferation and enhancing apoptosis in colon cancer cells (HCT116). Our results indicated that ZO significantly enhances the production of reactive oxygen species, lipid peroxidation (thiobarbituric acid reactive substance [TBARS]), and loss of cell viability; and reduces mitochondrial membrane potential and antioxidant levels (SOD, CAT, and GSH) in ZO‐treated HCT116 cells in a dose‐dependent (2.5, 5, and 10 µM) manner. Furthermore, ZO induces oxidative stress‐mediated apoptosis as evidenced by apoptotic morphological changes predicted by AO/EtBr, Hoechst staining and further confirmed by comet assay. Moreover, immunoblotting techniques showed that ZO treatment effectively enhances Bax, caspase‐9, and caspase‐3 expressions and decreases the expression of Bcl‐2 in colon cancer cells. Together, our results evidenced that the antitumor effects of ZO reduce cell proliferation and stimulate apoptosis through modulating pro‐ and antiapoptotic molecular events in HCT116 colon cancer cells. Therefore, based on our findings, ZO may be used as a therapeutic agent for the treatment of colon cancer.